As Micronarrativas em Portugal: de Almada Negreiros a Ana Hatherly - Rodrigues, B (2015)
Literary works and other manifestations that demonstrate, disseminate or stimulate the practice of extremely brief narrative texts have increasingly been gaining ground in the 21st-century. This phenomenon, which varies in intensity depending on the country – seemingly more substantial in the American continent and more timid in European countries –, has ramifications more or less on a global scale. Naturally, there has been, over the last few decades, a greater awareness of the dissemination of this type of productions, thanks to the visibility that new information technology, above all the Internet, has afforded. This tendency, however, just like any other human activity, is bound to have antecedents. To analyse its roots may help us to understand its relevance today. The research carried out here has as its object of study extremely brief narrative texts produced in Portugal. It focuses on a period of time which, it will be argued, is of utmost importance for the presence of micro-narratives in the Portuguese literary landscape: the period situated between the dawn of modernism at the beginning of the 1910s and the post-revolutionary moment when Ana Hatherly publishes the third volume of her overarching project entitled Tisanas, in 1980.